THE MILITARY REFORMS AND ACHIEVEMENTS OF ALAUDDIN KHILJI - Bilal Ahmad Mugloo (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Alauddin Khilji, the ruler of the Delhi Sultanate in medieval India, faced numerous military challenges during his reign. These challenges included defending against Mongol invasions, suppressing internal rebellions, expanding the boundaries of the Sultanate, and overcoming logistical obstacles. To address these challenges, Khilji implemented significant military reforms, such as establishing a standing army, implementing strict disciplinary measures, introducing the branding system for horses, and constructing strategic forts. These reforms played a crucial role in consolidating his power, expanding the Sultanate's territory, ensuring the effectiveness of the armed forces, and strengthening the stability of the Delhi Sultanate. Khilji's military strategies and decisions, including his aggressive expansionist policy and emphasis on defense, intelligence gathering, and resource utilization, contributed to his military successes and reshaped the socio-political dynamics of the Sultanate.